Kinetics of the epoxy-thiol click reaction initiated by a tertiary amine: Calorimetric study using monofunctional components - Meizoso Loureiro, Roi (2015)
An analysis of the kinetics of the epoxy-thiol reaction in a model stoichiometric system of monofunctional reagents, 3-mercaptopropionate (BMP) and phenylglycidylether (PGE) is reported. Benzyldimethylamine (BDMA) was employed as initiator in amounts ranging from 0.5 to 2 wt%. These formulations showed a kinetic behavior qualitatively similar to that of commercial adhesives and coatings formulated for a room-temperature cure. Isothermal DSC scans revealed the existence of a relatively long induction period preceding a fast autocatalytic reaction step. Dynamic DSC scans showed that the reaction was shifted to a lower temperature range by increasing the storage period of the initial formulation at 20 °C. This unusual kinetic behavior could be modeled assuming that thiolate anions, slowly generated during the induction period, initiated a fast autocatalytic propagation/proton transfer reaction. The kinetic model included a pseudo-steady state for the initiator concentration and an equilibrium reaction between epoxy and OH groups generated by reaction. A reasonable fitting of isothermal and dynamic DSC runs was achieved in a broad range of temperatures and amine concentrations. In particular, both the length of the induction time and the effect of the storage period were correctly predicted.